Clinical management of pregnancy in the obese mother: before conception, during pregnancy, and post partum. Issue 12 (December 2016) - Ma, Ronald Ching Wan; Schmidt, Maria Ines; Tam, Wing Hung; McIntyre, Harold David; Catalano, Patrick M
Summary: The global epidemic of obesity has led to an increasing number of obese women of reproductive age. Obesity is associated with reduced fertility, and pregnancies complicated by maternal obesity are associated with adverse outcomes, including increased risk of gestational diabetes, pre-eclampsia, preterm birth, instrumental and caesarean births, infections, and post-partum haemorrhage. The medical and obstetric management of obese women is focused on identifying, addressing, and preventing some of these associated complications, and is a daunting challenge given the high percentage of patients with obesity and few therapeutic options proven to improve outcomes in this population. The UK's National Institute for Health and Care Excellence guidelines and the American College of Obstetricians and Gynecologists recommend that all pregnant women follow a healthy diet, and consider at least half an hour of moderate physical activity per day during pregnancy. However, although obese women are often directed to seek the advice of a nutritionist and to limit gestational weight gain, guidelines for the management of pregnancy and delivery in this high-risk group are lacking. The post-partum period represents an important opportunity to optimise maternal health before the next pregnancy. As many of the physiological changes of pregnancy associated with maternal obesity are present from early pregnancy onward, reducing maternal obesity before conception is probably the best strategy to decrease the health burden associated with maternal obesity.